2020
DOI: 10.1177/1559827620911645
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Wellness: The Anesthesiologist’s Perspective

Abstract: Burnout syndrome results from unmanaged chronic workplace stress. It is characterized by emotional exhaustion, lack of a sense of personal accomplishment, and depersonalization. Burnout is associated with the development of poor work-related outcomes, mental health disorders, substance abuse, and cardiovascular disease. Burnout in physicians and other health care providers can negatively affect patient care. The prevalence of burnout in anesthesiology is among the highest of all medical specialties, with rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 63 publications
2
24
0
2
Order By: Relevance
“…Furthermore, several studies revealed the burnout of anesthesiologists worldwide [29,30]. Our study observed that surgery needing complicated preparation and maintenance such as lung resection and knee arthroplasty would inhibit more analgesic mode.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, several studies revealed the burnout of anesthesiologists worldwide [29,30]. Our study observed that surgery needing complicated preparation and maintenance such as lung resection and knee arthroplasty would inhibit more analgesic mode.…”
Section: Discussionmentioning
confidence: 72%
“…The stress hormone cortisol has also been shown to impair memory retrieval of well-learned memories in humans ( Wolf et al, 2004 ). And, literature on burnout finds that uncontrollable stress and feeling over-worked can disrupt not only cognitive performance but also interpersonal interactions and wellbeing ( Arnsten and Shanafelt, 2021 ; Romito et al, 2021 ).…”
Section: Brief Review Of Critical Literaturementioning
confidence: 99%
“…This is especially true of medical students and residents and other individuals in training or early in their medical careers who have been shown to experience very high levels of burnout. Other frontline physicians such as primary care physicians, emergency room physicians, and as Romito et al 6 point out in their article, anesthesiologists have also been shown to have high levels of burnout.…”
mentioning
confidence: 98%